Effect of nonsteroidal anti-inflammatory drugs on neonatal calf diarrhea when administered at a disease alert generated by automated milk feeders - A. Welk; M.C. Cantor; H.W. Neave; J.H.C. Costa; J.L. Morrison; C.B. Winder; D.L. Renaud (Journal of Dairy Science)
ABSTRACT: The objective of this randomized clinical trial was to assess whether early intervention with a nonsteroidal anti-inflammatory drug (NSAID) following a disease alert generated by automated milk feeders could reduce diarrhea severity and improve performance in dairy calves. A total of 71 Holstein calves were enrolled on an automated milk feeder (recorded milk intake and drinking speed) at 3 d of age and received up to 15 L/d (150 g/L) of milk replacer until 35 d of age. An alert that was previously validated as diagnostically accurate to identify calves at risk for diarrhea was used using automated milk feeder data (≤60% rolling dividends in milk intake or drinking speed over 2 d). At their first alert, calves were randomly allocated to receive a single subcutaneous injection of meloxicam (Metacam, Boehringer Ingelheim) at a rate of 0.5 mg/kg of BW (NSAID) or an equal volume of saline as a placebo control (CON). Fecal consistency was scored daily, and calves were diagnosed with diarrhea when they had loose feces for ≥2 d or watery feces for ≥1 d. Body weight was recorded at birth and weekly thereafter. A subset of calves (n = 32) were fitted with IceQube pedometers at 3 d of age to measure activity behaviors (lying time and step count). Mixed linear regression models were used to assess the association of study treatment with the duration of diarrhea after the alert and to evaluate the association of study treatment with milk intake, drinking speed, lying time, overall activity for 5 d following the alert, and ADG for 3 wk following the alert. On average, calves triggered an alert at (mean ± SD) 9.3 ± 2.3 d of age and were diagnosed with diarrhea at 9.6 ± 2.1 d of age. Diarrhea duration was similar between treatments (NSAID: 2.85 vs. CON: 2.94 ± 0.37 d), as were feeding behaviors (milk intake [NSAID: 8.2 vs. CON: 8.1 ± 0.4 L/d] and drinking speed [NSAID: 0.38 vs. CON: 0.37 ± 0.02 min/L]). Treatment was also not associated with ADG for the 3 wk after the alert (NSAID: 0.97 vs. CON: 0.97 ± 0.06 kg/d). However, calves provided an NSAID had reduced odds of being treated with electrolytes (odds ratio = 0.32, 95% CI: 0.10–0.98). In addition, calves provided an NSAID spent less time lying (NSAID: 17.64 vs. CON: 18.17 ± 0.19 h/day) and performed more steps over the 5 d following the alert (NSAID: 789.1 vs. CON: 628.0 steps/d), suggesting that CON calves may have been more lethargic. Overall, providing an NSAID at the time of a diarrhea alert did not affect diarrhea duration, feed intake, or growth. However, providing an NSAID increased activity in the 5 d following the alert, which may have reduced pain and symptoms of lethargy, indicating a milder response to the disease. We suggest that providing an NSAID at the time of diarrhea alert had little benefit on the calf; however, further work is needed to understand behaviors associated with malaise and pain in calves with diarrhea as well as the efficacy of NSAID under different management conditions.